19F NMR Spectroscopy Tagging and Paramagnetic Relaxation Enhancement‐Based Conformation Analysis of Intrinsically Disordered Protein Complexes. (26th November 2019) - Somlyay, Máté; Ledolter, Karin; Kitzler, Manuel; Sandford, Graham; Cobb, Steven L.; Konrat, Robert
Abstract: The combination of 19 F NMR spectroscopy tagging and paramagnetic relaxation enhancement (PRE) NMR spectroscopy experiments was evaluated as a versatile method to probe protein–protein interactions and conformational changes of intrinsically disordered proteins upon complex formation. The feasibility of the approach is illustrated with an application to the Myc‐Max protein complex; this is an oncogenic transcription factor that binds enhancer box DNA fragments. The single cysteine residue of Myc was tagged with highly fluorinated [ 19 F]3, 5‐bis(trifluoromethyl)benzyl bromide. Structural dynamics of the protein complex were monitored through intermolecular PREs between 19 F‐Myc and paramagnetic (1‐oxyl‐2, 2, 5, 5‐tetramethyl‐Δ3‐pyrroline‐3‐methyl)methanethiosulfonate (MTSL)‐tagged) Max. The 19 F R 2 relaxation rates obtained with three differently MTSL‐tagged Max mutants revealed novel insights into the differential structural dynamics of Myc‐Max bound to DNA and the tumour suppressor breast cancer antigen 1. Given its ease of implementation, fruitful applications of this strategy to structural biology and inhibitor screening can be envisaged. Abstract : Order from disorder : Protein–protein interactions and conformational changes of intrinsically disordered proteins upon complex formation can be probed through a combination of 19 F tagging and paramagnetic relaxation enhancement NMR spectroscopy experiments. The figure depicts the conformational change of the disordered part of Myc as DNA binds to the Myc‐Max heterodimer.